The Effects of Fenugreek Extract on Growth Performance, Serum Biochemical Indexes, Immunity and NF-κB Signaling Pathway in Broiler - Huang, Hui; Wang, Xia; Yang, Ling; He, Wenxiang; Meng, Tiantian; Zheng, Ke; Xia, Xin; Zhou, Yingjun; He, Jianhua; Liu, Chunming; Zou, Shengwen; Xiao, Dingfu (Frontiers in Veterinary Science, 2022)
In order to study the regulation of Fenugreek seed extract (FSE) on the immunity of broilers, and explore the appropriate amount of FSE in broilers' production, one-day-old yellow feather broilers with a total of 420 birds were randomly allocated into seven treatments. Each treatment had six replicates, with 10 birds per replicate. The two control groups were the basic fodder group fed with basal diet and the bacitracin zinc group added 30 mg/kg bacitracin zinc to the basal diet. Experimental groups included five levels of FSE (50 mg/kg, 100 mg/kg, 200 mg/kg, 400 mg/kg, and 800 mg/kg FSE to the basal diet, respectively). The pre-test period was 7 days and the formal test lasted for 56 days. The results showed that the average daily gain (ADG) of 50 mg/kg and 800 mg/kg FSE groups was significantly increased (P<0.01), and the feed to gain ratio (F/G) of FSE groups was significantly decreased (P<0.01) compared with the basic fodder and the bacitracin zinc groups. Compared with the basic fodder group, the serum total cholesterol (TC) content in the FSE groups was significantly decreased (P<0.05), the serum low density lipoprotein cholesterol (LDL-C) content of 50 mg/kg,100 mg/kg, and 800 mg/kg FSE groups was significantly lower than that of the basic fodder group (P<0.05). Compared with the basic fodder and bacitracin zinc groups, the serum immunoglobulins (IgG, IgM, IgA) content of 100 mg/kg, and 200 mg/kg FSE groups were significantly increased (P<0.05). Compared with the bacitracin zinc group, the serum interleukins (IL-1, IL-10) content of 400 mg/kg FSE group were significantly increased (P≤0.05), and the serum interferon-γ (IFN-γ) content of 100 mg/kg and 200 mg/kg FSE groups was significantly increased (P<0.05). Compared with the basic fodder group,the lower doses (0-400 mg/kg) of FSE had no significant effect on the mRNA expression of toll-like receptors 4/ myeloid differentiation factor 88/ nuclear factor-κB (TLR4/MyD88/NF-κB) signaling pathways (P>0.05). The 800 mg/kg FSE treatment group significantly increased the expression levels of NF-κB mRNA in the spleen of broilers (P<0.05). The zinc bacitracin group significantly increased the expression levels of MyD88 and NF-κB mRNA (P≤0.05).